2009
DOI: 10.3945/jn.109.104406
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Ghrelin Response after High-Fat Meals Is Associated with Decreased Satiety in Obese and Lean Chinese Young Adults ,

Abstract: Ghrelin and peptide tyrosine tyrosine (PYY) are known to affect appetite and body weight, but the acute effects of fat-rich and carbohydrate-rich meals on plasma ghrelin, PYY response, and appetite remain unclear. We hypothesized that obese individuals had impaired postprandial ghrelin and PYY response based on macronutrient content of meals, affecting appetite and energy intake. We conducted a randomized crossover trail comparing fasting ghrelin and PYY concentrations, postprandial ghrelin and PYY responses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 59 publications
5
23
0
1
Order By: Relevance
“…They found that acylated ghrelin levels dropped significantly after meal ingestion and remain decreased 2 h later in lean controls, whereas in obese individuals no changes of AG were observed at 30, 60 and 120 minutes after meal ingestion. The present study confirms these observations and previous reports that obesity can alter postprandial ghrelin response [7,8]. We also observed that the proportion between acylated and desacylated ghrelin are modulated by meal consumption in a different manner in obese and non-obese individuals.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…They found that acylated ghrelin levels dropped significantly after meal ingestion and remain decreased 2 h later in lean controls, whereas in obese individuals no changes of AG were observed at 30, 60 and 120 minutes after meal ingestion. The present study confirms these observations and previous reports that obesity can alter postprandial ghrelin response [7,8]. We also observed that the proportion between acylated and desacylated ghrelin are modulated by meal consumption in a different manner in obese and non-obese individuals.…”
Section: Discussionsupporting
confidence: 81%
“…partially confirm the hypothesis that the dysregulation of ghrelin secretion may reinforce obesity [8,9] and that the modulation of altered proportions of both ghrelin forms may be a new treatment strategy for obese individuals. Recently some studies have concentrated on the AG/DAG ratio and their impact on the pathogenesis of obesity [19][20][21].…”
Section: Prace Oryginalnesupporting
confidence: 68%
See 1 more Smart Citation
“…Nevertheless, it is reported that the postprandial blood levels of these gut hormones are significantly different between obese and lean rats or mice, and are regulated by the intake of macronutrients [27,28]. Evidence suggests that postprandial rather than fasting blood levels of ghrelin, PYY and NPY play an important role in regulating food intake and energy metabolism in rodents [29]. A prospective study on appetite-regulating hormones under fasting and postprandial conditions would help to elucidate whether LWDH has a regulatory effect on appetite and satiation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another study showed higher baseline leptin levels in obese subjects compared to lean subjects [15]. Furthermore, Yang et al [16] reported greater postprandial suppression of ghrelin in obese as well as lean subjects after a high carbohydrate meal rather than a high fat meal. However, obese individuals demonstrated less ghrelin suppression following either meal when compared to the lean subjects.…”
mentioning
confidence: 97%